Disparities in the access and provision of mental health services as part of primary health care: a case study of Ga-South district in the Greater Accra region - Adusei, Abena Boahemaa; Ayiku, Roberta Naa Barkey; Amarteyfio, Kezia Akosua Naa Amerley; Bondzie, Eugene Paa Kofi; Adjei-Banuah, Nhyira Yaw; Abdul-Samed, Abdul-Basit; Mirzoev, Tolib; Agyepong, Irene Akua (Frontiers in Public Health, 2025)
Mental illness can be as debilitating as physical ailments, yet many mental health patients lack access to quality mental health care in low- and middle-income countries. This study aimed to identify and characterize disparities in access to mental health care, as well as challenges in service provision, in the Ga-South district of Ghana. A qualitative case study design was used, employing purposive and snowball sampling to recruit participants. Sixteen in-depth interviews were conducted with 17 participants, which included one interview with 2 participants. The participants were mental health patients, caregivers of mental health patients, mental health advocates, health promotion officers, and psychiatric nurses in the Ga-South district of Ghana. The findings reveal that stigma, inadequate support, deficiencies in diagnosis and referral, and high treatment costs create substantial disparities in mental health care access. Stigma around mental health constrains both the provision of mental health care by nurses and healthcare-seeking efforts by patients. Diagnosis and referrals of mental health cases are sometimes deficient in the district, with some medical officers and midwives diagnosing mental health conditions inadequately before referrals to psychiatrists. Nurses on the wards also struggle to manage mental health cases, even after receiving mental health training from their facilities. Findings also reveal that some healthcare professionals sometimes exhibit apathy toward mental health issues. The cost of services and medications for patients is also high which prevents patients from seeking care. Additionally, a critical shortage of psychiatrists results in inadequate patient follow-up. The study underscores the urgent need for comprehensive reforms in mental health care delivery to promote inclusion and address disparity issues. It is necessary to ensure equitable access to quality mental health services by addressing workforce shortages and financial barriers, as well as enhancing awareness, training, and efforts to reduce stigma. Prioritizing these reforms will help to create a healthcare system that effectively supports mental health, promoting healthier communities and improving overall health outcomes.